Resistance is not Futile:Discovery and development of peptide antibiotics composed of D amino acids - Adaligil, Emel. (2017)
Abstract: Since the discovery of penicillin in 1928, many antibiotics targeting different kinds of bacterial species have been developed. Extensive and improper use of antibiotics has triggered a "bacterial resistance" problem. The biggest challenge in developing new antibiotics is that the bacterial strains may become resistant to newly developed drugs even during laboratory development before clinical trials in humans. Vancomycin is one of the "last resort" antibiotics used in the treatment of life threatening hospital infections. Since the isolation and identification of a vancomycin-resistant strain in 1988, it is of the highest and gravest of concern that vancomycin-resistance can be spread to multi-drug resistant pathogenic bacteria such as Methicillin-resistant Staphylococcus aureus (MRSA) that is responsible for lethal infections in immune-compromised subjects, such as those afflicted with AIDS, and organ transplant patients. In such a scenario, there will be no more available drugs for the treatment of such patients and the biggest advantage the modern medicine has thrived upon would be taken away. The aim of this dissertation is to develop stable, protease resistant peptides composed of D-amino acids as antibiotics that bind D-Alanyl-D-Alanine termini of vancomycin-sensitive bacteria and D-Alanyl-D-Lactate termini of vancomycin-resistant bacteria with a mechanism of action similar to that of vancomycin based on mirror-image phage display concept. We have identified several L-peptides that bind the enantiomer of vancomycin-sensitive and resistance bacterial cell wall termini by screening phage display libraries displaying 7-12 residue linear, cyclic and bicyclic random peptides against enantiomers of derivatives of the β-lactam antibiotic cephalosporin, that mimic the D-Ala-D-Ala termini of peptidoglycan structures in bacterial cell walls, crucial for crosslinking and providing structural integrity to the cell. In addition, enantiomers of the cell wall crosslinking pentapeptide precursors, including those that contain D-Ala-D-Lac were also used. After evaluating the binding specificity of each identified peptide to its target molecule via ELISA, a total of 94 peptides (linear, cyclic, and bicyclic) identified from such screen were synthesized as their mirror image versions (D-peptides). Antibacterial activity assays established that some of these D-peptides (linear, cyclic and bicyclic) have antibacterial activity against vancomycin-sensitive and vancomycin-resistant bacteria with a MIC values ranging from 8 μg/ml to 64 μg/ml. Taken together, we have a used a hitherto unused unified chemical-biological approach that can be used to generate a wide range of D-peptides that can act as antibiotics and will pave the way for a new family of antimicrobial compounds.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Chemistry.; Advisor: Krishna Kumar.; Committee: Joshua Kritzer, Tomi Sawyer, and Samuel Thomas.; Keyword: Chemistry.